2020
DOI: 10.1515/znc-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization of different yarrow species (Achillea sp.) and investigations into their antimicrobial activity

Abstract: Various Achillea species are rich in bioactive compounds and are important medicinal plants in phytotherapy. In the present study, Achillea millefolium L., Achillea moschata Wulfen, and Achillea atrata L. were compared with respect to their phenolic profile and antibacterial activity against gram-positive bacteria strains (Staphylococcus, Propionibacterium). Particular focus was given to A. atrata, which has hardly been studied so far. Based on the metabolite profile, A. atrata exhibited more similarities to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…The highest anti-radical capacity of the extracts was found in the ethyl acetate fractions of both species. The phytochemical comparison of these two Achillea species confirmed the findings of our previous study [34], indicating the differences in the occurrence of major phenolic components of aerial parts to be marginal. In contrast, the amounts of individual phenolic compounds appear to be species-specific.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The highest anti-radical capacity of the extracts was found in the ethyl acetate fractions of both species. The phytochemical comparison of these two Achillea species confirmed the findings of our previous study [34], indicating the differences in the occurrence of major phenolic components of aerial parts to be marginal. In contrast, the amounts of individual phenolic compounds appear to be species-specific.…”
Section: Discussionsupporting
confidence: 87%
“…Regardless of the species, the fractionation and subsequent phytochemical characterization revealed that luteolin, apigenin, nevadensin, and centaureidin were detected exclusively in the corresponding ethyl acetate fractions. A correlation between the contents of these phenolic compounds and an increased antimicrobial activity has already been demonstrated in our previous study [34]. It is also conceivable that an increased antioxidant capacity goes along with the occurrence of these four compounds, which are known as effective DPPH radical scavengers [37][38][39].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations